THE USE OF MULTIMEDIA IN ENGLISH LANGUAGE TEACHING: A CASE STUDY AT STATE JUNIOR HIGH SCHOOL 16 OF PALEMBANG - Ali, Muhammad (Politeknik Negeri Sriwijaya, 2022)
ABSTRACT: This study entitled the used of Multimedia in English Language Teaching (a case study at State Junior High School 16 of Palembang) is intended to figure out how the use of Multimedia in English language teaching to the first levels. Learning to read any language is a complex process that depends initially on multiple decoding skills. Once children are able to master decoding skills, the influence of other variables in the reading progress is more noticeable. Learning and teaching a foreign language needs a lot of patience, energy, time, creativity and competence. The success of the teaching and learning of foreign language skills including English is determined by a number of factors such as students, teachers, teaching methods, techniques, and instructional Multimedia. English teaching Multimedia are very important for teacher to help students acquire new concept of the skills and language competences. English has been taught at primary level due to its important role. English teachers in this level need more knowledge about children in mastering English. It is done because children have certain characteristics that differ from adult learners. There are still many fascinating discussions that might be interesting to find out the real situation in the implementation of Multimedia in English language teaching, especially to children. The study employed case study research design. The used of multimedia in English language teaching. There are some variable which observe by the researcher, there are: Computer, Internet, Print text, and Movie. According to the students’ competencies, the teacher builds up new atmosphere in teaching learning process by using pint text in reading, speaking, writing and vocabulary. The used of movie help the students in all competencies, such as reading, speaking, listening, writing and vocabulary teaching learning process. By using multimedia can beneficial for some students who can adjust the idea of teaching media that are fun, pleasure, and interesting. However, if these things are not entirely applied, challenges may appear in applying it. Keywords: English language, multimedia, teaching